Comparison of WHO, RECIST 1.1, EORTC, and PERCIST criteria in the evaluation of treatment response in malignant solid tumors - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2016)
AimTo compare response assessment according to the WHO, RECIST 1.1, EORTC, and PERCIST criteria in patients diagnosed with malignant solid tumors and who had received cytotoxic chemotherapy to establish the strength of agreement between each criterion.Materials and methodsSixty patients with malignant solid tumors were included in this retrospective study. The baseline and the sequential follow-up fluorine-18-fluorodeoxyglucose PET/computed tomography (CT) of each patient were evaluated according to the WHO, RECIST 1.1, EORTC, and PERCIST criteria. PET/CT images were used for both metabolic and anatomic evaluation. The concurrent diagnostic CT and MRI images (performed within 1 week of PET/CT) were also utilized when needed. The results were compared using the -statistics.ResultsThe response and progression rates according to the WHO criteria were 37 and 38%, respectively. The same ratios were also found for RECIST 1.1 (=1). The response and progression rates according to the EORTC criteria were 47 and 40%, respectively. When PERCIST criteria were used, one patient with progressive disease was upgraded to stable disease (=0.976). As we found the same results with WHO and RECIST 1.1 criteria, we used WHO criteria to compare the anatomic and metabolic criteria. When we compared the WHO and EORTC criteria, there was an agreement in 80% of the patients (=0.711). With WHO and PERCIST criteria, there was an agreement in 81.6% of the patients (=0.736).ConclusionSignificant agreement was detected when the WHO, RECIST 1.1, EORTC, and PERCIST criteria were compared both within as well as between each other.
Keywords: EORTC; F-18-FDG; PERCIST; PET; CT; RECIST 1; 1; WHO; POSITRON-EMISSION-TOMOGRAPHY; RECTAL-CANCER; PREDICTING RESPONSE; COLORECTAL-CANCER; F-18-FDG PET/CT; CLINICAL-TRIALS; CHEMOTHERAPY; THERAPY; PARADIGM; PROPOSAL